Competence-based Approach to Learning Outcomes Assessment: Russian Experience in Sociological Education - Margarita D. Bershadskaya; Alexandra V. Serova; Alexander Yu. Chepurenko; Elena A. Zima (Высшее образование в России, 2019)
The paper considers the methodological approaches to the description of the competency outcomes of education when implementing the federal standards of higher education on the example of the Sociology as an area of study. The authors have offered a methodic for assessment of the competences formation which is based on the so called indicators of achievement of each of the related competences and on the distribution of these indicators among all elements (modules) of the educational program of BA or MA in Sociology. In the paper, a list of indicators of universal (to be achieved in each higher education program regardless of the area) and general professional competences of the Bachelor’s and Master’s degrees in Sociology is proposed, as a result of monitoring and evaluation of several educational programs in the area of Sociology; moreover, the authors adduce the examples of content-related, concrete indicators of education called descriptors for competences. Besides, the paper describes the testing schemes which enable to adjust indicators of universal competences and to evaluate the level of competence of students who have completed the related educational level.